Themes in Soviet Marxist Philosophy
235 p.
Keywords: The Soviet philosophical scene has experienced remarkable growth since the innovations of the 50's and the renovations of the 60's. This volume of Sovietica is intended by the editors as a finger on the pulse of the Marxist-Leninist corpus philosophicum as we enter the 1970's. Published in the years between 1960 and 1970, the Filosofskaja en ciklopedija (FE) has replaced the Kratkij filosofskij slovar' (Short Philo sophic Dictionary: 1939, 1941, 1951 and 1954) and the Filosofskij slovar' (Philosophic Dictionary: 1963). It is an impressive work - 2994 pages in five volumes (I, 1960, 504 pp.; II, 1962, 575 pp.; III, 1964, 584 pp.; IV, 1967, 591 pp.; V, 1970, 740 pp.), with the editors and authors representing all the contemporary Soviet philosophers of note. The FE has been extensively reviewed in Kommunist (1972, 5, 119-127) and in Studies in Soviet Thought [beginning with SST 12 (1972) 4]. Restrictions of space have forced us to omit much that was originally to be included. The same limitations have obliged us to deviate from the initial methodological rule which was 'to include only complete, un abridged articles' - in order to avoid distortion by selection. Only two articles have been shortened: only the basic portion of 'science' has been included; we have dropped 'natural science', 'sciences on man and society', and 'classification of sciences' (a total of thirteen pages in Russian) - this last with regret and with apologies to Professor Kedrov.